Allodynia is associated with a higher prevalence of depression in migraine patients. (December 2014) - Louter, MA; Wardenaar, KJ; Veen, G; van Oosterhout, WPJ; Zitman, FG; Ferrari, MD; Terwindt, GM
Introduction: There is a strong association between migraine and depression. The aim of this study is to identify migraine-specific factors involved in this association. Methods: We conducted a cross-sectional study in a large, well-defined cohort of migraine patients ( n  = 2533). We assessed lifetime depression using validated questionnaires, and diagnosed migraine based on the International Classification of Headache Disorders III-beta criteria. Multivariate regression analyses were conducted. Results: Of the 2533 migraineurs that were eligible, 1137 (45%) suffered from lifetime depression. The following independent factors were associated with an increased depression prevalence: i) migraine-specific risk factors: high migraine attack frequency and the presence of allodynia, ii) general factors: being a bad sleeper, female gender, high BMI, being single, smoking, and a low alcohol consumption. Conclusion: This study identified allodynia, in addition to high migraine attack frequency, as a new migraine-specific factor associated with depression.